IMPLEMENTASI KEBIJAKAN PENERBITAN SURAT IZIN PENANGKAPAN IKAN (SIPI) DI JAWA TENGAH - Nurul Fauziah; Kismartini Kismartini (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2016)
The implementation of policy of the issuance of fish catching license (SIPI) in Central Java has not been in accordance with the prescribed rules. The implementation of policy of the issuance of fish catching license (SIPI) in Central Java reap many problems so that the background of this research. Research conducted aiming to analyze the implementation of policy of the SIPI issuance in Central Java, analyze the factors supporting and hindering the implementation of the policy, then it can be formulated based on the efforts that need to be done so that the implementation of policy can be effective. This research uses qualitative research by collecting data through observation, interviews, and documents. The results showed the implementation of the issuance of SIPI in Central Java is still there is a mismatch as well as the time and costs in the issuance of the permit. This happens because of the cultural community of fisherman themselves are difficult to understand the requirements and procedure for issuance of SIPI, the role of licensing services or brokers, the issuance of UU No. 23/2014, and the lack of human resources in the implementation of and the lack of human resources in the implementation of the issuance of SIPI in Central Java. Based on these concerns, there should be efforts to minimize the problems start, doing emotional approach with a way to communicate directly to change the paradigm and the culture of fishing communities in providing an understanding related to issuance of SIPI, evaluation of UU No. 23/2014, a watchful eye on the role of brokers, need additional human resources, and simplification of requirements and procedures for issuance of SIPI for effective policy implementation according to predefined rules.